A very powerful Case: the Theatre and the Sexual (Itinera, 2017)
Sexual theatre does not only have the advantage of effectively putting on stage the five senses, both among actors and between actors and the audience, it also derives great power from it. Firstly, it attains the noble, however rarely met ambition of performing arts: to stir the most intense emotions among the audience. Secondly, it naturally triggers, without any artificial device or bad faith, the utopia of the 70s’ avant-garde: the participation of the audience. This mechanism conceals the ultimate, political power of sexual theatre. To the extent the phenomenon of performing representation is the mirror image of the phenomenon of political representation, sexual theatre, after having transformed the audience into actors, invites voters to stand up, and become political actors. Sexual theatre re-energises tired representative democracies.